PEMILlHAN BAHAN PEMULIAAN UNTUK PEMBENTUKAN VARlETAS UNGGUL DISKRIMINATIF TUMPANGSARI: PADI + JAGUNG + UBlKAYU DI LAHAN KERING. I HASIL BIJI KERING JAGUNG - Abdul Bari; , Subandi; Endang Sjamsudin; , Supriyanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
Intercropping of Maize, Rice and Cassava is commonly practiced by subsistent farmers on upland agriculture in Indonesia. In general, grain yield of maize under intercropping is very much lower than under monoculture crop. This due to the fact that the variety of maize planted under intercrop was bred and selected under elite, monoculture crop condition. Three field experiments to screen maize breeding materials planted in association with rice and cassava were carried out in Pekalongan (Lampung), October 1993 - November 1994. Three out of 29 entry of maize were selected, MC-1 (optimistic), Wiyasa (neutral) and ICS1 Arj15F (pessimistic). Performance test on grain yield relative stability for three selected materials have to be done before practicing any form of improvement by means of selection.